FREEDOM OF EXPRESSION AND FAKE NEWS: IRREPARABLE CONSEQUENCES OF DISINFORMATION? (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
Freedom of expression is one of the fundamental rights guaranteed by the Brazilian Federal Constitution; however, it is not an absolute right, considering that there are limitations when the expression exceeds the truth and legality of information through the sharing of fake news.The dissemination of fake news has become a significant challenge in the digital age, resulting in impacts on public policies and democratic issues due to the influence these falsehoods have on portions of the population. In this context, this study seeks to address the following question: Is the subsequent accountability for committed abuses an effective tool to control fake news? Or, once spread and taken as true, do they have irreparable consequences?The methodology used is the hypothetical-deductive method, starting from the hypothesis that, although freedom of expression is a fundamental right, its use for deliberate misinformation requires accountability measures. The study was developed through bibliographic research, and legislative and case law analysis.The relevance of the topic is justified by the growing dissemination of false information on social networks, especially in political contexts, which may undermine the credibility of democratic institutions. It is concluded that freedom of expression must be guaranteed but with responsibility, ensuring the population's right to access legitimate information and protecting democracy from the harmful effects of disinformation.